2019
DOI: 10.4103/abr.abr_236_18
|View full text |Cite
|
Sign up to set email alerts
|

Successful Myomectomy in the Second Trimester of Pregnancy

Abstract: The prevalence of uterine myomas during pregnancy is estimated to be small. However, a significant fraction of these could lead to pregnancy complications. Myomectomy is rarely performed during pregnancy because of fear of miscarriage and the risk of uncontrolled hemorrhage necessitating hysterectomy. This article reports on a case of myomectomy of subserous leiomyoma that was causing septic necrosis, leukocytosis, rise of inflammatory markers (erythrocyte sedimentation rate and C-reactive protein), and pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Other cases have also described the use of vasopressin and intermittent compression of uterine arteries to control blood loss,6 however, concerns have been raised regarding the reduction in fetal oxygenation. Intraoperative tocolytics1 2 and the use of progesterone8–10 following the procedure to reduce the risk of miscarriage have also been described, though there remains no consensus on optimum management 6. Additionally, successful laparoscopic myomectomy11–13 has also been reported in the literature; however, it is reserved for those with smaller, subserous pedunculated9 and would not be suitable for the described case.…”
Section: Discussionmentioning
confidence: 99%
“…Other cases have also described the use of vasopressin and intermittent compression of uterine arteries to control blood loss,6 however, concerns have been raised regarding the reduction in fetal oxygenation. Intraoperative tocolytics1 2 and the use of progesterone8–10 following the procedure to reduce the risk of miscarriage have also been described, though there remains no consensus on optimum management 6. Additionally, successful laparoscopic myomectomy11–13 has also been reported in the literature; however, it is reserved for those with smaller, subserous pedunculated9 and would not be suitable for the described case.…”
Section: Discussionmentioning
confidence: 99%
“…Myomectomy in pregnancy has been reported for the treatment of intractable pain that has failed conservative management, torsion, renal compromise secondary to obstruction, and septic necrosis [17][18][19][20][21]. Limited retrospective studies have evaluated pregnancy outcomes in women who undergo first or second trimester myomectomies and while successful pregnancy outcomes have been reported conservative management is recommended and surgery is indicated only on a caseby-case basis [18,22,23].…”
Section: Discussionmentioning
confidence: 99%
“…However, in cases with torsion of pedunculated myoma or persistent symptoms not responding to conservative treatment, myomectomy should be considered. 4,5 Since Lucas et al 6 first reported laparoscopic myomectomy during pregnancy in 1994, the major advantages of this minimally invasive approach, including minor postoperative pain and quick recovery, have been widely accepted.…”
Section: To Editormentioning
confidence: 99%
“…Although conservative treatment is considered as golden standard, surgery is not routinely recommended because of the risks of severe hemorrhage, pregnancy loss, preterm labor, and uterine rupture. However, in cases with torsion of pedunculated myoma or persistent symptoms not responding to conservative treatment, myomectomy should be considered 4,5 . Since Lucas et al 6 .…”
mentioning
confidence: 99%